2022
DOI: 10.3389/fninf.2022.837549
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Workflow for Performance Benchmarking of Neuronal Network Simulations

Abstract: Modern computational neuroscience strives to develop complex network models to explain dynamics and function of brains in health and disease. This process goes hand in hand with advancements in the theory of neuronal networks and increasing availability of detailed anatomical data on brain connectivity. Large-scale models that study interactions between multiple brain areas with intricate connectivity and investigate phenomena on long time scales such as system-level learning require progress in simulation spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…Figure 7 shows the performance benchmarks of the multi-area model on CPUs conducted on JURECA-DC using the benchmarking framework beNNch (Albers et al, 2022 ). For both network states, the optimal configuration of the hybrid parallelization is achieved with 8 MPI processes per node and 16 threads per task, thus making use of every physical core of the machine while avoiding hyperthreading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows the performance benchmarks of the multi-area model on CPUs conducted on JURECA-DC using the benchmarking framework beNNch (Albers et al, 2022 ). For both network states, the optimal configuration of the hybrid parallelization is achieved with 8 MPI processes per node and 16 threads per task, thus making use of every physical core of the machine while avoiding hyperthreading.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this implementation only allowed MPI buffers to grow, but not to shrink. Albers et al ( 2022 ) identified that this puts unnecessary strain on the MPI communication. They therefore introduced spike compression which only sends one spike to each target MPI process, which has the necessary knowledge on the target threads saved in an additional data structure.…”
Section: Discussionmentioning
confidence: 99%
“…To fully exploit their capabilities in a benchmark comparison one needs to optimize for each simulator and use case. Second, the community has not agreed on standardized benchmark models (Albers et al, 2022; Ostrau et al, 2022; Kulkarni et al, 2021; Steffen et al, 2021). The RBN is widely used in computational neuroscience.…”
Section: Discussionmentioning
confidence: 99%
“…To fully exploit their capabilities in a benchmark comparison, one needs to optimize for each simulator and use case. Second, the community has not agreed on standardized benchmark models (Kulkarni et al, 2021;Steffen et al, 2021;Albers et al, 2022;Ostrau et al, 2022). The RBN is widely used in computational neuroscience (cf.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%